Bis(di-tert-butyl)-4-dimethylaminophenylphosphine as electrolyte additive to improve the electrochemical performance of LiNi0.8Co0.1Mn0.1O2. (10th February 2023) - Zhuang, Yan; Zhao, Yuhui; Bao, Yingqing; Zhang, Wei; Guan, Mingyun
Highlights: Bis-4TMPA was added into the electrolyte to improve the electrochemical performance of NCM811. Bis-4TMPA could undergo electrochemical oxidation, promote partial electrolyte solvolysis and participate in the formation of the SEI film. The phosphine group in Bis-4TMPA can react with the oxygen species released from the cathode surface, which protects electrolytes from oxidative decomposition. The nitrogen-containing group in Bis-4TMPA can react with HF to reduce the corrosion on the electrode. The reversibility of the H2 ⇋ H3 phase transition was improved when the NCM811 cycled in the electrolyte with Bis-4TMPA, which reduced the generation of microcracks. Abstract: To improve the performance of LiNi0.8 Co0.1 Mn0.1 O2 cathode material for Lithium-ion batteries, Bis(di-tert-butyl)-4-dimethylaminophenylphosphine (Bis-4TMPA) was added in the electrolyte as an additive. The phosphine group in this molecule can react with the oxygen species released from the cathode surface, which protects electrolytes from oxidative decomposition. Meanwhile, the nitrogen-containing group can react with the produced HF to reduce its corrosion on the electrode. A high capacity retention rate of 76.3% was achieved after 400 cycles (1C=200 mAh g −1 ) from the LiNi0.8 Co0.1 Mn0.1 O2 with the addition of 0.5wt% Bis-4TMPA. This was higher than that of the electrolyte without Bis-4TMPA (69.1%). LSV (linear sweep voltammetry) and XPS (X-ray photoelectron spectroscopy) indicated that the additive could undergo electrochemical oxidation, promote partial electrolyte solvolysis and participate in the formation of the CEI (cathode electrolyte interface) film. The FIB-SEM and HRTEM results indicate that the reversibility of the H2 ⇋ H3 phase transition was improved when the cathode cycled in the electrolyte with Bis-4TMPA, which reduced the generation of microcracks. SEM results show that the cathode after cycling in the electrolyte containing Bis-4TMPA still maintained a well structure with intact particle morphology. In summary, the use of Bis-4TMPA as an electrolyte additive improves the performance of LiNi0.8 Co0.1 Mn0.1 O2 lithium-ion batteries.